Ações relativas à filiação: investigação, contestação, impugnação e anulação - Holanda, Vanessa de Maria Outtone (2009)
The present work analyzes the procedural aspects in actions relâted to filiation, in special those in which the objective is its establishment and opposition, conceming the reality of the filiation rights, introduced by the Brazilian Constitution and Civil Code in force nowadays. Apart from legislative changes, that reflected the social modifications revealing a new concept of family, the evolution of medicine, allowing the discovery of biological descendants by the ADN analyzes and artificial procreation revealed the need to be revisited the procedural aspects of such actions in arder to promote a systematization of the subject. Initially, it is presented the historical and legislative evolution of the Brazilian rights offiliation, as well as the ways of voluntary recognition ofnone-marital children and their main features. Just because the action of establishment and opposition of the filiation are in fact actions abolir the state of persons there are some features, in particular regarding res iudicata, that distinguishes from other actions. The deep analysis of the identified elements of each of these actions, beyond the applicable jurisdiction ruIes; the judgment and its effects on the patemity and maternity actions, defense of patemity; defense of the recognition; annulment of civil registry intends the elements of the substantive law to the procedural institutes available in the procedural law. In Suill, this work intents to demonstrare that the current Brazilian civil procedure provides the required elements to the full realization of the rights in discussion of those kind of actions, and it is possible that the rights arising from the filiation is safe, without aiming the security of legal relationships, according to the current procedurallaw